Perencanaan Perpustakaan dalam Meningkatkan Minat Membaca Anak Muda Milenial di Gampong Meunasah Rayeuk Lhoksukon - Saputra, Andika (Medan Resource Center, 2023)
lanning is the fundamental framework in facilitating the learning process and cultivating the reading interest of millennial youths to equip them for the future. Thus, planning serves as the cornerstone. Library Planning to Enhance the Reading Interest of Millennial Youths in Meunasah Rayeuk Village, Lhoksukon. Based on observations regarding the enhancement of learning interest among millennial youths, especially in Meunasah Rayeuk Village, Lhoksukon, it is evident that thorough planning is essential for future improvements. The Lhoksukon District Library has initiated this program to shape character and enhance the human resources of the younger generation for the future. When young individuals develop a passion for reading, the golden generation of the future begins to emerge. Therefore, promoting reading education and culture is a hallmark of intelligent nations. Let us seize this opportunity to elevate the reading interest of the younger generation in Meunasah Rayeuk Village, Lhoksukon.